2022
DOI: 10.1155/2022/8210599
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Retinal Vessel Caliber with Age-Related Macular Degeneration

Abstract: Purpose. Evaluate the relationship between retinal vascular caliber and age-related macular degeneration (AMD) severity or progression. Methods. A retrospective secondary analysis of 1172 fundus photographs and clinical data from the prospective Age-Related Eye Disease Study (AREDS). Central retinal artery equivalent (CRAE), central retinal vein equivalent (CRVE), and arteriole-to-venule ratio (AVR) were measured using the Parr–Hubbard–Knudtson formula. Univariate and multivariate regressions were used to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…In a previous study, low serum PTH levels were suggested to be associated with retinal vascular diameters and a decreased risk of retinal microvascular impairment [ 70 ]. Pathogenesis of ARMD has proposed that retinal vascular diameters was associated with the severity of ARMD [ 71 ]. Trinh et al demonstrated that retinal vascular length and vascular diameter were all significantly decreased and narrowed in patients with ARMD [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, low serum PTH levels were suggested to be associated with retinal vascular diameters and a decreased risk of retinal microvascular impairment [ 70 ]. Pathogenesis of ARMD has proposed that retinal vascular diameters was associated with the severity of ARMD [ 71 ]. Trinh et al demonstrated that retinal vascular length and vascular diameter were all significantly decreased and narrowed in patients with ARMD [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Calcium is an essential micronutrient that participates in numerous vital physiological functions, and although most studies on the role of calcium have focused on bone health, attention has recently been paid to the effects of dietary calcium and calcium supplements on other health outcomes [ 414 ]. It has been suggested that dietary calcium is related to blood pressure by regulating intracellular calcium in vascular smooth muscle cells [ 415 ]. It is also related to retinal vascular diameter and length, which are important in patients with age-related macular degeneration, as this decreases and narrows during the course of the disease [ 416 , 417 ].…”
Section: The Importance Of Dietary Patterns On Visual Healthmentioning
confidence: 99%
“…OCT angiography has been utilized to demonstrate that flow impairment of the choriocapillaris around GA lesions could predict progression of GA [40]. Retinal vessel caliber has also been associated with AMD severity; narrower arterioles have been noted eyes with geographic atrophy, but are not necessarily predictive of the development of central GA [41].…”
Section: Monitoring Progression Of Geographic Atrophymentioning
confidence: 99%